Allelopathic Effects of Chromolaena odorata (L.) King & Robinson on Seed Germination and Seedlings Growth of Paddy and Barnyard Grass - Suwal, Meena Maiya; Devkota, Anjana; Lekhak, HD (Scientific World, 2010)
Viable seeds of paddy and barnyard grass in different concentrations of aqueous extracts ( 2, 4, 6, 8 and 10 %) of leaf, stem and root of Chromolaena odorata were germinated at room temperatures. The leaf extract had strong inhibitory effect on seed germination as well as linear growth of paddy and barnyard grass. The order of inhibition was leaf >stem >root on both tested seeds. Allelopathic effect increased with increased concentration of the extracts. Key Words: Allelopathy; Paddy; Barnyard grass; Aqueous extract; Root length; Shoot length. DOI: 10.3126/sw.v8i8.3854 Scientific World Vol.8(8) 2010 pp.73-75